Associations Between Vision, Hearing, and Olfactory Impairment With Handgrip Strength. (15th April 2019) - Gopinath, Bamini; Liew, Gerald; Burlutsky, George; Mitchell, Paul
Objectives: We aimed to assess the cross-sectional associations between sensory impairments (vision, hearing, and/or olfactory loss) and handgrip strength.Method: In the Blue Mountains Eye Study, 947 participants aged 65+ years had handgrip strength measured using a dynamometer. Visual impairment was defined as visual acuity <20/40 (better eye), and hearing impairment as average pure-tone air conduction threshold >25 dBHL (500-4, 000 Hz). Olfaction was measured using the San Diego Odor Identification Test.Results: Marginally significant associations between sensory impairment and handgrip strength were observed after multivariable adjustment. For example, women with two or three sensory impairments had lower adjusted mean handgrip strength (17.47 ± 0.5 kg) versus women who had no sensory loss (18.59 ± 0.3 kg; p = .06) or only one sensory impairment (18.58 ± 0.3 kg; p = .05), respectively. No significant associations were observed in men.Discussion: Women who had multiple sensory impairments had reduced muscle strength as indicated by ~1.1 kg lower mean handgrip strength.